The Impact of Brexit on EU Trade Policy - De Ville, Ferdi (2019)
There has been increased interest in trade policy following the UK’s EU membership referendum. However, relatively little scholarly analysis has been produced on how Brexit will affect EU trade policy. Instead, the received wisdom has been that Brexit will shift the EU’s trade policy position in a less liberal direction. This is based on a ‘static’ analysis where the UK variable is simply removed from the figurative ‘function’ determining EU trade policy. We argue that this neglects the potential role of more ‘dynamic’ effects. First, the negotiations to determine the nature of the EU–UK future economic partnership are likely to involve a lengthy process with a still uncertain, and possibly evolving, destination. The outcome and process of arriving there will influence how economic operators and policymakers adapt their preferences and behaviour, including through possible relocation and the formation of new alliances. This will shape EU trade policy in potentially counterintuitive ways. Second, the absence of clear material structures from which actors can ‘read’ their interests highlights the importance of considering the role of ideas and political framing. How the vote for and consequences of Brexit are interpreted will likely shape what is considered an appropriate policy response. Examining EU trade policy since the Brexit vote, the article finds that rather than push the EU in a more illiberal direction, the referendum result has been used to reinforce the European Commission’s external liberalisation agenda. The Commission’s discursive response to Brexit and Donald Trump has been to portray the EU as a champion of free trade in an era of global populism.